Chronic Stress-Induced Depression and Anxiety Priming Modulated by Gut-Brain-Axis Immunity - Westfall, Susan; Caracci, Francesca; Estill, Molly; Frolinger, Tal; Shen, Li; Pasinetti, Giulio M. (Frontiers in Immunology, 2021)
Chronic stress manifests as depressive- and anxiety-like behavior while recurrent stress elicits disproportionate behavioral impairments linked to stress-induced immunological priming. The gut-brain-microbiota-axis is a promising therapeutic target for stress-induced behavioral impairments as it simultaneously modulates peripheral and brain immunological landscapes. In this study, a combination of probiotics and prebiotics, known as a synbiotic, promoted behavioral resilience to chronic and recurrent stress by normalizing gut microbiota populations and promoting regulatory T cell (Treg) expansion through modulation of ileal innate lymphoid cell (ILC)3 activity, an impact reflecting behavioral responses better than limbic brain region neuroinflammation. Supporting this conclusion, a multivariate machine learning model correlatively predicted a cross-tissue immunological signature of stress-induced behavioral impairment where the ileal Treg/T helper17 cell ratio associated to hippocampal chemotactic chemokine and prefrontal cortex IL-1 production in the context of stress-induced behavioral deficits. In conclusion, stress-induced behavioral impairments depend on the gut-brain-microbiota-axis and through ileal immune regulation, synbiotics attenuate the associated depressive- and anxiety-like behavior.